BIAYA AGENSI DAN POTENSI KEBANKRUTAN BANK UMUM KEGIATAN USAHA 1 DAN 2 DI INDONESIA - Ahmad Rizal Solihudin; Permata Dian Pratiwi (Universitas Ahmad Dahlan, 2021)
The Bank’s risk of bankruptcy has risen due to the pandemic's impact on financial distress. This study aims to evaluate the effectiveness of risk control mechanisms on the banking sector listed in the Indonesia Stock Exchange (IDX). Agency cost which could indicate the ability to reduce the risk of bank bankruptcy was proxied by commissioner fee, insider ownership, and audit committee and then assigned as the variables of the study. This study employed quantitative methods, by using panel data regression analysis. Bank Umum Kegiatan Usaha 1 (BUKU 1) and Bank Umum Kegiatan Usaha 2 (BUKU 2) were used as samples for this study. The results show that commissions and insider ownership have no significant impact on financial distress at BUKU 1 and BUKU 2. While the Audit Committee has a significant impact on the value of financial distress at BUKU 1 and BUKU 2. In The perspective of the X-Score model, agency costs have no significant effect on the likelihood of bankruptcy at BUKU 1 and BUKU 2.